CORPORATE INTEGRITY PRACTICES: APPLICATION OF SOCIAL CONTRACT THEORY IN THE MALAYSIAN PUBLIC ORGANISATIONS - Nurhidayah Yahya; Salwa Zolkaflil; Nur Aima Shafie; Afzal Izzaz Zahari (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Nowadays, corruption is seen as usual, phenomenal, and endemic. It is pinpointed as the main obstacle that prevents government services from being delivered to the population. Thus, the establishment of effective measures to prevent corruption is much needed. One of the measures is by having corporate integrity in the organisation. Corporate integrity is proven to have positive effects on organisations, which eventually helps improve performance, accountability, and sustainability. Corporate integrity has three dimensions: ethical foundation, culture, and risk management. The ethical foundation is vital as a fundamental of corporate integrity practices in organisations. A solid integrity institution further helps to advance ethical culture. Thus, a robust foundation and culture improve ethical risk management. All the dimensions and components attribute to the corporate integrity practices of organisations. Thus, future research could embed these three dimensions when examining the level of corporate integrity practices.